Studi Komparasi Pendidikan Kewarganegaraan pada Anak Usia Dini di Negara Indonesia dengan Negara Arab - Wikan Sasmita; Fitta Nurisma Riswandi (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2023)
Early childhood citizenship education in Indonesia with Arab countries in the background of state and citizen challenges globalization affects the growth, physical and spiritual development of children such as norms, behaviours and life values have an impact on the progress of the country. Research is used to improve the life of the Indonesian state while Arab countries master 21st-century skills. The research method uses literature studies with the aim of exploring early childhood citizenship education in the two countries. The results of the study stated that the country's vision and mission have a golden Indonesia target in 2045, while the Arab country has a target of superior education services in 2030. Education uses the independent learning curriculum and the student profile of Pancasila, the country of Indonesia.In contrast, the Arab country uses superior services equitable and inclusive quality education to increase lifelong learning opportunities. The focus of achieving early childhood development in Indonesia includes religion and morals, Pancasila, physical motor, cognitive, language, and social-emotional, while the Arab country achieves standards: knowledge, behaviour, skills, making citizens suitable, productive, and effective—Indonesian citizenship education, consisting of Pancasila values and Pancasila student profiles. While Arab citizenship education contains citizenship, national identity and culture, exploration of the interaction between the state and society makes a good citizen. In conclusion, the education of early childhood citizenship of the Indonesian state with Arabs can make citizens of character and citizenship.